IMPLEMENTASI PENGEMBANGAN WILAYAH SUNGAI DURIAN SEBAGAI KAMPUNG RENDANG - Suci Andriani; Febri Yuliani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This study discusses the implementation of the development of the Durian River Basin as a Kampung Rendang. The purpose of this study (1) to determine the implementation of the development of the Durian River Basin as Kampung Rendang, (2) to determine the factors that hinder the implementation of the development of the Durian River Basin as Kampung Rendang. The research method used is a qualitative method. Based on the research results, the implementation of the development of the Durian River Basin as Kampung Rendang has been implemented well. This can be proven by the existence of Kampung Rendang, an area in Payakumbuh City, namely Nagari Sungai Durian where the area is dominated by rendang IKMs that have existed since 2015. Furthermore, the factors that hinder the implementation of the Development of the Durian River Basin as a Rendang Village are the Covid-19 pandemic. which causes delays in various activities related to production to promotion, lack of human resources, and the lack of knowledge of the Rendang IKM about the use of technology. Keywords: Implementation, Development, Rendang